G155(P) Changing hearts and minds? gp practices and young people making change happen together. (27th April 2015) - Cheetham, M; Nixon, E; Percival, J; Davison, B; Ellins, A
Abstract : Aims: 75% of adult mental health problems appear in adolescence, but young people report difficulties accessing appropriate health services. GP practices are not always seen as responsive, and barriers to access are reported by young people. Greater understanding is required of the benefits, pitfalls and possibilities of young people's engagement in general practice. This study examines the effects of a collaborative, peer led intervention to improve primary health care for young people with mental health concerns. Methods: Focus group discussions were held with young people trained as Changemakers, to explore the reported benefits and risks of volunteering. 1:1 interviews were conducted with representatives from partner organisations, GPs and practice managers to explore what difference, if any, young people's input had made, for whom, and how. Results: Our findings demonstrate the potential of the programme, including You're Welcome, to drive positive changes in general practice, led by young people, supported by voluntary sector partners. We outline the challenges and opportunities of the Changemakers model and the factors influencing its success, including the support and guidance required. We report young people's suggestions for new ways of working, their ideas for engaging young people, and recommendations for health service delivery. Conclusions: Traditional models of patient involvement do not work with young people. This peer-led intervention offers a promising alternative, stimulating practical and attitudinal changes in the delivery of young people friendly primary care. It requires whole practice investment of time and resources, and a willingness to embrace change. The resulting efforts to encourage access by young people, including those with mental health problems, will potentially benefit the wider practice population.